HUBUNGAN ANTARA PERILAKU BULLYING VERBAL DENGAN IMPLEMENTASI KASIH DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DI SMA NEGERI 1 MANADO - Lorentia Sinarya Marcus; Aljuanika Ertamaya Ering; Irene Preisilia Ilat (Jurnal Ilmiah Wahana Pendidikan, 2026)
The purpose of this study is to determine the relationship between verbal bullying behavior and the implementation of love in Christian Religious Education learning among Christian students at SMA Negeri 1 Manado. This study is a quantitative research employing a correlational method, conducted at SMA Negeri 1 Manado in 2026. Data were collected through questionnaires using a Likert scale administered to 225 respondents. Based on the product-moment analysis, a correlation coefficient value of -0.677 was obtained, indicating a strong, significant, and inversely proportional or negative relationship between verbal bullying behavior and the implementation of love. This implies that the lower the level of students' verbal bullying behavior, the more optimal the implementation of love will be in Christian Religious Education learning. Consequently, it is concluded that efforts to significantly reduce verbal bullying actions serve as a primary indicator for enhancing the implementation of love in Christian Religious Education learning at SMA Negeri 1 Manado. Based on these findings, it is recommended that the school principal consider these results when designing more structured student affairs and character-building programs. Additionally, Christian Religious Education teachers are encouraged to determine appropriate teaching methods, such as project-based learning, to foster a conducive school environment. Lastly, this study provides deep insights for future researchers to be utilized as a relevant reference or scientific comparison.